The Electrical Motorcycle Charger for Application in a Residence - Chaiyan Jettanasen; Chaichan Pothisarn (My University, 2020)
The aim of this paper is to design the charger for an electric motorcycle and analyze the behavior of voltage and current value during charging. The AC voltage supply from a residence is converted to DC voltage to charge the energy storage system by controlling the voltage and current values suitable for the charge process in all periods. The designed charger is based on the principle of a buck converter with using constant current and constant voltage technique in order to charge a 12 V, 21 Ah lead-acid battery inside the electric motorcycle. By considering the results, the first state of battery charging is a constant current mode by using the current of 5 A with the initial voltage of 55 V. In the second mode, the battery charging is done by constant voltage of 72 V and the current is reduced until the battery is full. Moreover, the charging time is about 6-8 hours.
Keywords: Constant current; Constant voltage; Constant (computer programming); Advanced Battery Technologies Research